From eligibility assessment to intervention for students with autism spectrum disorder. Issue 2 (9th November 2022) - Goldstein, Sam; Sellars, Tiffany; Velez, Alexandro
Abstract: The mean age of identification for autism spectrum disorder (ASD) occurs during the months before children enter kindergarten. The incidence and prevalence of "autistic behaviors" in the general population are not fully understood, however, census‐matched studies of these behaviors have yielded important new data. As children presenting with behaviors characteristic of ASD enter school, school psychologists are increasingly faced with the assessment and determination of individuals with disabilities improvement act (IDEIA) eligibility, often with students yet to be formally diagnosed with ASD. In many US states, a clinical diagnosis of ASD is not required for a child's eligibility to be served under the category of other health impaired as autism. Nor does a diagnosis of ASD automatically qualify a student as eligible under IDEIA. Eligibility hinges on educational impact. This article briefly reviews the current state of knowledge as it relates to understanding and evaluating children with suspected ASD in the schools, offers a framework for assessment, and discusses a set of proposed guidelines to assist in effectively utilizing assessment data in the development of individualized education plan goals. Practitioner Points: The determination of eligibility and the integration of specialized educational programs as part of comprehensive education for students with autism spectrum disorder (ASD) continues to evolve. The mean age of identification for ASD occurs during the months before children enter kindergarten. ASD is also associated with a wide range of internalizing and externalizing behavioral problems. The interpretation and application of IDEIA guidelines for determining eligibility as autism varies greatly from state to state and even between school districts within a state. It is still the case that there is at times a confusing relationship between clinical/medical diagnosis and care, and eligibility determination, and specialized educational processes.